0398 Is Increased Serum Prolactin Associated with Excessive Daytime Sleepiness? A Proof-of-Concept Analysis. (25th May 2022) - Mogavero, Maria; Cosentino, Filomena; Lanuzza, Bartolo; Tripodi, Mariangela; Lanza, Giuseppe; Aricò, Debora; DelRosso, Lourdes; Pizza, Fabio; Plazzi, Giuseppe; Ferri, Raffaele
Abstract: Introduction: With this study we aimed to: 1) identify subjects with hyperprolactinemia in a clinical sample of patients; 2) compare the neurologic, psychiatric, and sleep conditions found in patients subgrouped by excessive daytime sleepiness (EDS) and hyperprolactinemia; 3) identify patients with hyperprolactinemia and EDS not supported by the presence of any other neurologic, psychiatric, or sleep disorder, or substance/medication use. Methods: A retrospective chart review of inpatients was carried out in order to identify all patients in whom the prolactin (PRL) serum levels were determined. A total of 130 subjects were retrieved: 55 had increased levels of PRL while the remaining 75 participants had normal PRL levels. Results: EDS was reported by 32 (58.2%) participants with increased PRL and 34 (45.3%) with normal PRL. Obstructive sleep apnea or other sleep or neurologic/psychiatric conditions could explain EDS in all participants with normal PRL. Among subjects with increased PRL, eight had no other neurologic/psychiatric or sleep disorder (or drug) potentially causing EDS; these participants, at polysomnography, had time in bed, sleep period time, and total sleep time longer than those with EDS associated to another condition. Conclusion: These findings can be considered as a preliminary indication of a role of hyperprolactinemia in EDS and represent a basis for future controlled studies able to test in a reliable, objective, and methodologically more appropriate way this hypothesis. Support (If Any): This study was partially supported by a fund from the Italian Ministry of Health "Ricerca Corrente" (RC n. 2764026) (Drs. Cosentino, Aricò, Lanuzza, Lanza, Tripodi, and Ferri)